STRATEGI PEMERINTAH DAERAH DALAM PENATAAN PEDAGANG KAKI LIMA (PKL) MELALUI PENDEKATAN GAYA KEPEMIMPINAN DEMOKRATIK (STUDI PADA PEMERINTAH KOTA BANDUNG) - Nurhandini, Minati Ayu; Susiamti, Indri; Febrinanda, Satrya Tidyas (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to find out, describe and analyze how the arrangement of street vendors is carried out by the Bandung City Government using a democratic leadership style approach. This research uses qualitative research using descriptive methods. Data collection used was through observation, interviews and documentation. The focus of this research includes (1) the Bandung City Regional Government's strategy in structuring street vendors in Bandung City through a democratic leadership style. (2) supporting and inhibiting factors in the process of structuring street vendors in Bandung City.Based on the research results, it can be seen that the Bandung City Government's strategy in structuring street vendors is quite good, namely by forming a PKL Task Force which is a special task force formed from several SKPD which has the task of assisting the Mayor of Bandung in structuring and coaching street vendors which includes planning, structuring, guidance and supervision. The leadership style used by the Mayor of Bandung in implementing the strategy for structuring street vendors in Bandung City reflects a democratic leadership style with the decision-making process being carried out based on joint decisions and including the participation of subordinates and the street vendors themselves, the communication process carried out is quite effective and reaches all parties in a persuasive manner , there is supervision both directly and indirectly, as well as providing motivation by setting satisfactory final goals and providing consistent promises to street vendors.Keywords: Strategy, Street Vendor Arrangement, Democratic Leadership Style